Inhibition of DNA-dependent Protein Kinase Catalytic Subunit by Small Molecule Inhibitor NU7026 Sensitizes Human Leukemic K562 Cells to Benzene Metabolite-induced Apoptosis - 游浩 孔萌萌 王立萍 肖潇 廖汉林 毕卓悦 燕虹 王红 汪春红 马强 刘燕群 毕勇毅 (Journal of Huazhong University of Science and Technology. Medical sciences, 2013)
Benzene is an established leukotoxin and leukemogen in humans. We have previously re- ported that exposure of workers to benzene and to benzene metabolite hydroquinone in cultured cells induced DNA-dependent protein kinase catalytic subunit （DNA-PKcs） to mediate the cellular response to DNA double strand break （DSB） caused by DNA-damaging metabolites. In this study, we used a new, small molecule, a selective inhibitor of DNA-PKcs, 2-（morpholin-4-yl）-benzo[h]chomen-4-one （NU7026）, as a probe to analyze the molecular events and pathways in hydroquinone-induced DNA DSB repair and apoptosis. Inhibition of DNA-PKcs by NU7026 markedly potentiated the apoptotic and growth inhibitory effects of hydroquinone in proerythroid leukemic K562 cells in a dose-dependent manner. Treatment with NU7026 did not alter the production of reactive oxygen species and oxidative stress by hydroquinone but repressed the protein level of DNA-PKcs and blocked the induction of the kinase mRNA and protein expression by hydroquinone. Moreover, hydroquinone increased the phos- phorylation of Akt to activate Akt, whereas co-treatment with NU7026 prevented the activation of Akt by hydroquinone. Lastly, hydroquinone and NU7026 exhibited synergistic effects on promoting apop- tosis by increasing the protein levels of pro-apoptotic proteins Bax and caspase-3 but decreasing the protein expression of anti-apoptotic protein Bcl-2. Taken together, the findings reveal a central role of DNA-PKcs in hydroquinone-induced hematotoxicity in which it coordinates DNA DSB repair, cell cycle progression, and apoptosis to regulate the response to hydroquinone-induced DNA damage.